KETEPATAN DALAM PREPARASI–DETERMINASI FOSIL FORAMINIFERA PLANKTON SEBAGAI PENENTU UMUR RELATIF BATUAN DAN LINGKUNGAN PENGENDAPAN - Iwan Prabowo (PETROGAS: Journal of Energy and Technology, 2020)
Foraminifera fossils will provide information on the relative age and depositional environment in the rock layers. foraminifera Fossil itself consists of two types, plankton and benthic foraminifera, which in a rock cannot be determined easily. Required methods are used to be able to decipher fossil foraminifera in the rock bodies. This method is called microfossil preparation. The precision in the execution process of the preparation will be very helpful in the process of further analysis of the fossil, which is the stage of determination. This stage will determine genus to species (taxonomy) of an organism based on the characteristics of each foraminifera. Each of the characteristics of foraminifera will show a unique tendency, both in the habitat when the organism is still alive until it can undergo fossilization.